Efficacy of a Direct Aspiration First-Pass Technique (ADAPT) for Endovascular Treatment in Different Etiologies of Large Vessel Occlusion: Embolism vs. Intracranial Atherosclerotic Stenosis - Liao, Geng; Zhang, Zhenyu; Zhang, Guangzhi; Du, Weijie; Li, Chaomao; Liang, Hanxiang (Frontiers in Neurology, 2021)
Background and Aims—Aspiration thrombectomy is an effective method of recanalizing large vessel occlusion (LVO). However, the efficacy of a direct aspiration first pass technique(ADAPT) for recanalization of LVO of different etiologies is not properly understood. Methods—The prospectively collected database on aspiration thrombectomy as a first-line approach was reviewed retrospectively. We defined two groups of enrolled patients: the embolism-related occlusions (EMB-O) group and the intracranial atherosclerotic stenosis (ICAS)-related occlusion (ICAS-O) group. Baseline characteristics, procedural variables, and postprocedural variables were collected. Multivariate logistic regression analysis was used to identify first-pass recanalization predictors. Results—Of 114 registered patients, 94 were eligible for this study（51 patients in the EMB-O group and 43 patients in the ICAS-O group). Achieving successful reperfusion immediately after direct aspiration was more frequent in the EMB-O group than in the ICAS-O group (64.71% vs. 27.91%, respectively, P = 0.006), with fewer additional rescue treatments needed (35.29% vs. 70.09%, respectively, P = 0.001). The EMB-O group also showed a higher final successful reperfusion rate (96.8% vs. 74.41%, P = 0.006). However, the 90-day good functional outcomes were not affected by the groups.Independent predictors of first-pass success of aspiration included the isolated middle cerebral artery site of occlusion, embolic etiology, and use of larger bore catheters. Conclusions—The efficacy of ADAPT recanalization approach was better in EMB-O than in ICAS-O. In case of embolic etiology and the isolated MCA site of occlusion, using a larger aspiration catheter for direct aspiration thrombectomy may be reasonable.